Pro Microsoft power platform : solution building for the citizen developer - Pearson, Mitchell; Knight, Brian, 1976-; Knight, Devin; Quintana, Manuel (Apress, 2020)
Become a self-sufficient citizen developer by learning the tools within the Microsoft Power Platform and how they can be used together to drive change and multiply your productivity. Learn about PowerApps for building applications, Power Automate for automating business processes across those applications, and Power BI for analyzing results and communicating business intelligence through compelling visuals. By understanding the purpose and capabilities of these tools, you will be able to enhance your organization's visibility into key areas and make informed business decisions in a timely matter. This book is divided into four parts and begins in Part I by showing you how to build applications through PowerApps. You will learn about screens and controls, application sharing and administration, and how to make your applications accessible from mobile devices such as phones and tablets. Part II is about creating workflows using Power Automate that implement business logic across your applications. Part III brings in dashboards and data analysis, showing you how to connect to a data source, cleanse the data from that source, and drive decision making through interactive reports and storytelling. Part IV brings together all the pieces by showing the integrations that are possible when all three tools are combined into a single solution. You will: Understand the need for the citizen developer in today's business environment Organize and plan the building of line-of-business applications with PowerApps solutions Replace wasteful paper processes with automated applications built in PowerApps Automate workflows across processes with Power Automate Communicate analytical results through visualizations and storytelling Integrate PowerApps, Power Automate, and Power BI into solutions that multiply productivity.